Analisis Keefektifan Pengabdian Masyarakat pada Kegiatan Workshop AKM Guru SMP Mapel Bahasa Indonesia Kabupaten Semarang - Supriyadi Supriyadi; Roudloh Muna Lia; Ani Rusilowati; Wiwi Isnaeni; Wardani Rahayu; Suraji Suraji; Nur Sholihin (Unri Conference Series: Community Engagement, 2021)
The ideal condition is that teachers must be competent in conditioning students to be ready to face AKM. The current condition, the ability of teachers in developing assessment instruments is still low. They prefer shortcuts using a collection of questions sold in the market. Therefore, this community service activity is focused on providing guidance for junior high school teachers in preparing tests to face the AKM. The method used to achieve the objectives of this activity is a lecture with an in-on-in pattern. Documents that need to be prepared so that the service runs effectively are preparing powerpoint materials and supporting materials (observation sheets and questionnaires). All participants' responses to the AKM surgical workshop showed a positive response (with a percentage above 50%), except for one variable that received a low score, namely the login problem. The results of the documentation analysis showed that all participants collected the complete set of questions completely. The accuracy of writing the grid is in the range of 69% - 75% and the accuracy of writing the questions lies in the range of 84% - 100%. Based on the results of the questionnaire and the results of document analysis, it can be concluded that community service in AKM workshop activities is quite effective.